Vocal Music in Autism Therapy: Progress and Potential - Peng, Edison; Fan, Xiujun (International Journal of Innovative Research in Medical Science, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by challenges in social interaction, communication, and repetitive behaviors. Over time, the understanding of ASD has evolved, moving beyond early misconceptions to a more comprehensive view of its diverse symptoms and potential therapeutic strategies. Despite notable advancements, current interventions remain limited, highlighting the need for more innovative and effective approaches. This paper explores the therapeutic potential of music, with a focus on vocal music, in individuals with ASD. It examines the correlation between music therapy and improvements in emotional regulation, social skills, and communication abilities among autistic individuals. Additionally, the paper investigates the possible underlying mechanisms of vocal music therapy, including how it engages both hemispheres of the brain, enhances neuro-connectivity, and promotes the release of endorphins that contribute to emotional well-being. The potential of AI technology to personalize and optimize music therapy interventions is also explored. This review aims to synthesize the growing body of evidence supporting music, particularly vocal music, as a valuable tool in autism therapy, offering promising avenues for enhancing the quality of life for individuals on the autism spectrum.